Chemical Composition, Cytotoxicity and Colorectal Carcinoma Effects of Etlingera velutina Essential Oil: A Pre-clinical Trial Study. Issue 5 (3rd September 2022) - Luo, Xiaolong; Ye, Yunjie; Deng, Lingzhi; Ji, Xuelin; Lin, Fulin
Abstract: Etlingera velutina belongs to the Zingiberaceae family. The plant is known as a potent agent for snakebite and food flavoring in the east of Asia. In this study, the essential oil from the rhizomes of E. velutina was obtained using the hydro-distillation assay. The chemical composition of the oil was identified by chromatographic methods of GC/FID and GC/MS. The MTT assay was run to evaluate the cytotoxicity effect of the essential oil. The oil consists of sesquiterpene hydrocarbon. α-Cubebene (57.4%) and 2-undecanone (28.6%) were the major compounds for the rhizome oil. The MTT assay was run to treat the cell lines with essential oil for evaluation of the cytotoxicity and anti-human colorectal carcinoma properties. The IC50 of essential oil was 241 and 214 μg/mL against ileocecal colorectal adenocarcinoma (HCT-8 [HRT-18]) and Burkitt's lymphoma (Ramos.2G6.4C10) cell lines, respectively. The results showed a dose-dependently on The viability of malignant colorectal cell lines in the presence of essential oil. The obtained results revealed the essential oil of the rhizomes of E. velutina is a potent agent against colorectal carcinoma.